Фішинг - як шахрайство у мережі - Демидов, З. Г.; Demydov, Z. G.; ORCID:https://orcid.org/0000-0003-2821-8047; Колмик, О. О.; Kolmyk, О. О.; ORCID: http://orcid.org/0000-0003-0401-9588 (Study of modern problems of civilization : The V th International scientific and practical conference (Oslo, Norway, 19-23 October 2020). – Oslo, 2020. – P. 448-450, 2020)
Опис фішингу, як шахрайської схеми, його варіації і способи уникнення.

Description of fishing as a fraudulent scheme, its variations and ways to avoid it.

Описание фишинга, как мошеннической схемы, его вариации и способы избежания.
Демидов, З. Г. Фішинг - як шахрайство у мережі / З .Г. Демидов, О. О. Колмик // Study of modern problems of civilization : The V th International scientific and practical conference (Oslo, Norway, 19-23 October 2020) / Library of Congress Cataloging-in-Publication. – Oslo, 2020. – P. 448-450.
Keywords: фішинг; data; фишинг; fraud; шахрайство; дані; fishing; мошенничество; данные; Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина